Monitoring and conservation of soils as a component of a sustainable management for agroecosystems at the local level - Dmytruk, Yu. M.; Semenchuk, V. G. (AgroChemistry and Soil Science, 2021)
The article assesses the prospects of local and regional agroecosystems to provide modern measures to improve the quality of land and soils. The authors applied the analysis (induction and deduction) of guiding and normative documents and current publications of both Ukrainian and European on the organization of sustainable use of soils and the priority of their protection. It is important to remember, that the United Nations (U.N.) sustainable development goals (SDGs, indicator 15.3.1) have land degradation neutrality by 2030. A serious aspect of the article is the assessment of the possibilities of Ukrainian agriculture to implement a system of sustainable soil management at the local level in the near future. It is determined that drivers for soil management of agroecosystems, which determine the agenda for all land users and landowners are follows: (1) global processes and geopolitical significance of agriculture; (2) characteristics of soils as a natural object, in particular, their irreplaceability, non-renewability and performance of global biosphere functions; (3) national features, including the lack of real monitoring, gaps in legislation and non-compliance with existing regulations and acts and the land market. Therefore, there is a need for precise legislation to protect and preserve soils, as well as the implementation of agricultural technologies that will ensure a land degradation neutrality and soil sequestration of carbon. Given the uncertainty about the functioning of real soil monitoring at the state level, we consider it promising to organize soil monitoring as a local network. This means that the creation of a components of a specific soil management system should be provided by land users. The authors are convinced that experimental stations in the structure of NAAS should maintain / create their own database. Based on such a database it will be possible to effectively ensure sustainable soil management, namely: to assess soils current state at the moment, ecosystem services from soils, to predict the dynamics of soil indicators, to simulate different variants of their changes and so on. The costs of such a local GIS are offset by gains, including profits from business activities for many years to come. Due to the increased attention to soil organic carbon reserves (introduction of carbon taxes, restrictions on greenhouse gas emissions), it is urgent to assess and forecast the processes of carbon emission-sequestration and appropriate soil capabilities for a particular type of land use. Soil scientists are ready to develop a method of data collection and local GIS, taking into account the specifics of the type of agriculture.